Comparison of different methods for estimating total energy expenditure for brief bouts of high intensity intervals - Kilian, Y.; Koehler, K.; Wahl, P.; Zinner, C.; Sperlich, B.; Mester, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
O2 uptake remains the most popular method to estimate energy expenditure. Although O2 uptake provides an excellent representation of aerobic ATP turnover, it does not represent the energy expenditure (EE) by rapid anaerobic glycolytic ATP turnover. The quantification of total EE for exercise and recovery includes the measurement of exercise O2 uptake and excess post oxygen consumption (EPOC) along with anaerobic glycolytic ATP turnover. Scott et al. (2006) used and critically discussed these measurements to determine EE for a single brief bout of high intensity intervals. However the problems emerging with the used of these parameters might be even bigger when estimating the EE of several bouts of high intensive work due to the estimation of anaerobic EE from Äblood lactate levels. The aim of the present study was to compare the anaerobic and total EE calculated by different methods. Methods: Nine healthy competitive young cyclists took part in this study (14.4 ± 1.1 years; VO2peak: 59.6 ± 9.1 mL*kg-1*min-1; peak power output (PPO): 4.2 ± 0.5 W*kg-1). The high intensity training consisted of 4x4 min intervals at 90-95 % PPO separated by 3 min of active rest. Capillary blood from the earlobe was collected for the analyses of blood lactate pre, post warming-up (WU) and after each 4 min exercise bout. O2 consumption was recorded continuously during the exercise. Aerobic, anaerobic EE and EPOC were calculated according to Scott et al. (2006). Äblood lactate was obtained by a) subtracting WU lactate from peak interval lactate concentration, b) subtracting the previous interval lactate from peak interval lactate, c) treating Äblood lactate obtained the first interval as representative for all intervals. In addition, EE of the first interval was multiplied by 4 (d). Results: Total energy expenditure was a) 1824 ± 512 kJ, b) 1752 ± 522 kJ, c) 1781 ± 531 kJ and d) 1801 ± 564 kJ. Significant differences were found between method a) and b). Based on a total work 334 ± 73 kJ, average cycling efficiency was between 18.3% (b) and 19.1% (a). Conclusion: For estimating EE for repeated bouts of high intensity intervals it is possible to treat the first interval as representative for total EE. Even though there are significant differences between a) and b), these differences (72 kJ) are clinically not relevant.